Deficiency of (33P)2MeS-ADP Binding Sites on Platelets with Secretion Defect, Normal Granule Stores and Normal Thromboxane A2 Production - Cattaneo, Marco; Lombardi, Rossana; Zighetti, Maddalena L; Gachet, Christian; Ohlmann, Philippe; Cazenave, Jean-Pierre; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1997)
By the term “Primary Secretion Defect” (PSD), we mean a common heterogeneous group of congenital defects of platelet secretion, characterized by a normal primary wave of platelet aggregation induced by ADP and other agonists, a normal concentration of platelet granule contents, and normal production of thromboxane A2. The biochemical abnormalities responsible for PSD are not well known. Since a secretion defect similar to PSD is found in platelets that are severely deficient of binding sites for the ADP analogue 2MeS-ADP and do not aggregate in response to ADP, we tested the hypothesis that PSD platelets have moderately decreased 2MeS-ADP binding sites, which may be sufficient for normal ADP-induced aggregation but not for potentiating platelet secretion. The specific binding of [33P]2MeS-ADP to platelets from 3 PSD patients (347,443 and 490 sites/platelet; KD 2.8-3.9 nM) was lower than to platelets from 24 normal subjects (647 [530-1102]; KD = 3.8 [2.3-7.3]) (median [range]). Normal values were found in a fourth PSD patient (710; KD 3.7). The degree of inhibition of PGE1- induced cAMP increase by 0.1 |μM ADP was lower in patients than in controls. The secretion induced by the endoperoxide analogue U46619 from normal, acetylsalicylic acid-treated platelets under conditions that prevented the formation of large aggregates was potentiated by 1 fimol/1 ADP and inhibited by apyrase. These findings indicate that a partial deficiency of the platelet ADP receptor(s) might be responsible for the defect of platelet secretion in some PSD patients and that ADP potentiates platelet secretion independently of the formation of large aggregates and thromboxane A2 production.